The international politics of the united states and guidelines for constituting an international political authority as Caritas in Veritate - Calcín Figueroa, Eduardo (2010)
September 01, 2010, Barack Obama officially announced the end of the combat mission in Iraq.  American soldiers returned home after seven years in Iraqi territory. It described this fact as a “historic moment”. But the words of the spokesman of U.S. State Department, P. J. Crowley “This is not the end of the U.S. mission in the country “ giving rise to the analysis. This we do in this article. In turn, the announcement of former U.S. President G. Bush to establish “new world order” leads us to consider whether it is in line with the will of Pope Benedict XVI when he proposes the establishment of an “international political authority” in the latest social encyclical, Caritas in veritate.